A TUF Sell: Transportation Utility Fees as User Fees for Local Roads and Streets. (October 2016) - Voulgaris, Carole Turley
Currently, more than 1.5 million people in the United States contribute to the maintenance of their local roads and streets through transportation utility fees charged on their monthly municipal utility bills. The fees are assessed for each property based on a particular land-use characteristic (the fee's basis ). Although their use continues to spread, transportation utility fees have faced legal challenges that generally relate to the basis a city uses to assess the fee and have limited their widespread application. This article examines the bases used by 34 cities in the United States to implement transportation utility fees and discusses how each basis relates to the success of transportation utility fees in the cities that have implemented them and in other cities that may consider adopting them.